REAKSI PASAR MODAL DARI DAMPAK PERISTIWA HARI BESAR AGAMA ISLAM TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SAHAM PERUSAHAAN INDEKS JII YANG TERDAFTAR DI BURSA EFEK INDONESIA - Septiana Endang Subekti; Ika Yustina Rahmawati (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2020)
The purpose of this study is to analyze the capital market reaction from the impact of religious holidays which will be indicated by the presence or absence of abnormal return and trading volume activity. The sample used is the Jakarta Islamic Index (JII). This type of research is event study so that the observation period is used to see reactions before and after the event occurs. The events used in this study were the Birthday of the Prophet Muhammad, Isra Mi'raj, Eid al-Fitr, Eid al-Adha and Islamic New Year. The observation period used is from 2014 to 2017. The research period used was 7 days before the event and 7 days after the event. Data sources are obtained from Yahoo Finance, Sahamok.com and IDX. The data used in this study are secondary data, such as stock closing prices, IHSG closing prices and stock trading volume. The analytical tool used to test the hypothesis in this study is a paired t-test. The results showed that Eid al-Adha holidays had a significant difference to the abnormal return and trading volume activity before and after holidays. There were no significant differences in the abnormal return and trading volume activity before and after the Miraj Isra holiday. While the birthday of the Prophet Muhammad SAW, Eid holidays and Islamic New Year holidays there is no significant difference between abnormal stock returns and there are differences in trading volume activity before and after holidays.